Arctic animals in relation to climatic fluctuations - Vibe, Christian (Meddelelser om Grønland, 1967)
Abstract A study of the East Greenland Ice in Davis Strait makes it possible to recognize three main drift-ice stages which play an important role for climate and ecology in all Greenland. A). The drift-ice stagnation stage (approx. 1810- 60). The East Greenland Ice does not advance far north into Davis Strait where the Canadian Current has a dominating influence. The climate of northern West Greenland is relatively cold, dry and stable. The populations of sea mammals and sea birds concentrate at central West Greenland. The winter climate is favourable for the Reindeer in central and northern West Greenland, and the population increases and culminates. The population of white Arctic Fox increases and culminates in southeastern Canadian Arctic. The white percentage increases in West Greenland. The Cod occurs along the coast of southern West Greenland, but it is not abundant, except for short periods with little drift-ice. The drift-ice is relatively stable throughout the winter off Northeast Greenland where the climate is favourable for the Reindeer and the Musk Ox. The populations increase. B). The drift-ice pulsation stage (approx. 1860-1910). The ice of the Arctic Ocean drifts into the Atlantic in larger amounts than before. The East Greenland Current and the East Greenland Ice advance far north into Davis Strait either early or late in summer. The populations of sea mammals and sea birds decrease in central West Greenland. The climate becomes relatively unstable and wet. The wet winters are unfavourable for the Reindeer in West Greenland and the population decreases. The population of white Arctic Fox decreases in Canadian Eastern Arctic and that of blue Arctic Fox increases in central and northern West Greenland. The white percentage stagnates or decreases in northern West Greenland. Cod occur only occasionally in short periods with early drift-ice in Davis Strait. The drift-ice moves relatively fast off Northeast Greenland where the population of Musk Ox stagnates owing to wet winters. The Reindeer becomes extinct in North east Greenland. The population of Greenland Whale stagnates in the Atlantic region. C). The drift-ice melting stage (approx. 1910-1960?). The East Greenland Ice decreases in Davis Strait where the Irminger Current has a dominating influence on climate and production. The populations of sea mammals and sea birds increase in northern West Greenland and in East Greenland. The Reindeer population of West Greenland has ample summer grazing, but the winter pastures are often covered by snow and ice-and the population stagnates in all West Greenland, except for the short dry period 1910- 20. The population of white Arctic Fox increases and culminates in all eastern Canadian Arctic and in Northeast Greenland, and that of blue Arctic Fox in all West Greenland. The white percentage decreases in central and increases in northern West Greenland. Cod occur abundantly along the coast of West Greenland and multiply in Greenlandic waters. The population increases in periods with little or early drift ice and decreases in periods with late drift-ice in Davis Strait. Northeast Greenland has ample vegetation and the Musk Ox population usually thrives and increases, but is often threatened by catastrophes in wet autumns and winters when Greenland Sea has little or no drift-ice. At present a new "drift-ice stagnation stage" is beginning (approx. 1960-?). (See also the summary p. 193).